2019
DOI: 10.1071/py18113
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of general practice management and team care arrangements over time in New South Wales, Australia

Abstract: The number of older people living with chronic health conditions is increasing in Australia. The Chronic Disease Management (CDM) items program was introduced to the Medicare Benefits Schedule (MBS) to encourage a more structured approach to managing patients with chronic conditions. Initial uptake was slow and recent research has suggested that uptake is decreasing. This paper examines: person MBS CDM claims in NSW between 2006 and 2014 — using baseline survey data (2006–09) from the Sax Institute’s 45 and Up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…A qualitative review of QI programs in Australia similarly identified the need for external support, accurate data and reporting, education and change champions in addition to financial incentives [ 18 ]. Government-funded initiatives such as heart health assessments, health assessments for 45–49-year-olds, GP management plans and home medication reviews have only had partial uptake and mixed evidence of success [ 8 , 27 , 28 ]. One potential driver of their mixed success is that they are still fee-for-service activities and do not support GPs to adopt quality-focused models of care [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative review of QI programs in Australia similarly identified the need for external support, accurate data and reporting, education and change champions in addition to financial incentives [ 18 ]. Government-funded initiatives such as heart health assessments, health assessments for 45–49-year-olds, GP management plans and home medication reviews have only had partial uptake and mixed evidence of success [ 8 , 27 , 28 ]. One potential driver of their mixed success is that they are still fee-for-service activities and do not support GPs to adopt quality-focused models of care [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative review of QI implementation in Australia identi ed the need for external support, accurate data and reporting, education and change champions in addition to nancial incentives (18). Other government-funded initiatives such as heart health assessments, health assessments for 45-49-year-olds, GP management plans and home medication reviews have similarly only had partial uptake and mixed evidence of success (8) (24).One potential driver of their mixed success is that they are still fee-for-service activities and do not support GPs to adopt quality-focused models of care. The Federal "Health Care Homes" pilot and a proposed voluntary patient enrolment scheme aligned to a patient 'complexity' payment both offer options for value-based care and a departure from the prevailing fee-for-service paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on the impact of GPMP items demonstrated mixed outcomes with limited effectiveness for multi-provider collaboration; they were mainly used for administrative purposes rather than clinical motivations [ 8 ]. From 2006–2014 there was an overall doubling in the proportion of initial claims for GPMP or TCA (11.3% to 22.4%), with the highest uptake found: (i) in those aged 80–84 years; (ii) in people with diabetes; (iii) in those with lower physical functioning; and (iv) in people on lower incomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study looking at uptake of five or more physiotherapy claims under a GPMP in patients aged 85 years or older found this was associated with fewer avoidable hospitalisations [ 7 ]. Aside from one heart failure study, the benefit of GPMPs for management of cardiovascular disease (CVD) is uncertain [ 9 , 15 ]. Given the overall purpose of the GPMP to improve management of chronic care needs, goals, action, treatment, and services, the objectives of this study were to: Identify differences in socio-demographic and clinical characteristics in people with or at elevated risk of CVD by receipt of a GPMP.…”
Section: Introductionmentioning
confidence: 99%